RELIABILITY ANALYSIS FOR CRITICAL COMPONENTS ON THE RSG-GAS PRIMARY COOLING SYSTEM - Entin Hartini; Mike Susmikanti (SIGMA EPSILON - Buletin Ilmiah Teknologi Keselamatan Reaktor Nuklir, 2018)
ABSTRACTRELIABILITY ANALYSIS FOR CRITICAL COMPONENTS IN PRIMARY RSG-GAS COOLING SYSTEM. Reliability is the probability that a system will function normally when it is used for the desired time period under specific operating conditions. This study aims to analyze the reliability, distribution function of damage and rate of damage by using the frequency data of damage, downtime and time data between the damage of each component on the primary cooling system RSG- GAS. The methodology used is the Test of damage distribution estimated as an exponential distribution. Test the exponential distribution using the Bartlett test. Further estimation of data distribution parameters. Based on the parameters of the data distribution, the reliability and rate of damage can be calculated for the critical component of the primary cooling system. Damage data is obtained from maintenance data for core 70 until 88 (2010-2015). The results showed that in the primary cooling system the highest failure occurred for component JE-01 (AP01-02) with downtime = 112  (day) and failure  frequency presentation = 75%. The failure rate (λ) of 0.000215438 with the reliability value for the last year amounted to 99.83%. Keywords: Downtime, Damage frequency, Reliability, maintenance, RSG-GAS